Evaluation of Occupational Health Safety Management System in Hospitals in Banda Aceh City - Mutiawati, Cut; Mariana, Mariana; Mahidin, Mahidin (International Journal of Social Service and Research, 2023)
The most dominant hospital activity actors at risk of occupational safety accidents (SMK3) are hospital employees such as nurses, cleaning services, patients and visitors. The purpose of this study was to evaluate the application and factors affecting the implementation of occupational health and environmental safety management systems at dr. Zainal Abidin Regional General Hospital, Meuraxa Hospital and Banda Aceh Mother and Child Hospital. The data collection technique uses a mix method that combines quantitative and qualitative data with sequential explanatory strategies. The legal basis is Permenkes No. 66 of 2016, and the data was analyzed using the Likert scale method points 1-5 through SPSS version 26. The results of research at RSUDZA, RSIA, and RSUDM Banda Aceh show that the application of SMK3 is good to very good. However, there are several inhibiting factors that need to be considered by the hospital in order to improve the implementation of the Occupational Safety and Health Management System (SMK3) at RSUDZA, RSIA, and RSUDM Banda Aceh, some improvements can be recommended. First, RSUDZA needs to ensure the stability of K3 field officers and improve the marking of K3 signs. In addition, the unification of the drug room with pharmacy employees must be separated to be more effective. RSIA needs to obtain budget for ceiling repairs so as to block various small dirt falling from roof gaps, avoid splashing rainwater falling through the roof insulators or regulators of heat and cold coming from the roof, roof frame covers to make the space neater and cleaner, sound dampers, both generated by rainwater and other sounds and rearrange the right material placement. RSUDM needs to overcome solid waste piles, improve the marking of K3 rooms, and improve the arrangement of parking areas. In addition, it is important to hire additional security personnel in the ER. All these improvements are expected to improve occupational safety and health conditions in hospitals.